SALL4‐related gene signature defines a specific stromal subset of pancreatic ductal adenocarcinoma with poor prognostic features - Angélique Vienot; Franck Monnien; Caroline Truntzer; Virginie Mougey; Adeline Bouard; Jean‐René Pallandre; Chloé Molimard; Romain Loyon; Kamal Asgarov; Gerlinde Averous; François Ghiringhelli; Frédéric Bibeau; et al. (Molecular Oncology, 2023)
Pancreatic ductal adenocarcinoma (PDAC) is marked by molecular heterogeneity and poor prognosis. Among the stemness‐related transcription factors, Spalt‐like Transcription Factor 4 (SALL4) is correlated with unfavorable outcomes; however, its roles in PDAC remain unclear. SALL4high expression defines a PDAC subpopulation characterized by a shortened patient survival. Although SALL4 expression was mostly evaluated in tumor cells, our findings identify this embryonic transcription factor as a new biomarker in PDAC‐derived stroma. Gene expression analysis reveals that the SALL4high PDAC subset is enriched in cancer stem cell properties and stromal enrichment pathways; notably, an interaction with cancer‐associated fibroblasts (CAF) activated by TGF‐β. A particular oncogenic network was unraveled where Netrin‐1 and TGF‐β1 collaborate to induce SALL4 expression in CAF and drive their cancer‐stemness‐promoting functions. A 7‐gene stromal signature related to SALL4high PDAC samples was highlighted and validated by immunochemistry for prognosis and clinical application. This SALL4‐related stroma discriminated pancreatic preinvasive from invasive lesions and was enriched in short‐term survivors. Our results show that SALL4 transcriptional activity controls a molecular network defined by a specific stromal signature that characterizes PDAC invasiveness and worse clinical outcomes.